Cellulosic-crystals as a fumed-silica substitute in vacuum insulated panel technology used in building construction and retrofit applications - Tetlow, David; Simon, Lia De; Liew, Soon Yee; Hewakandamby, Buddhika N.; Mack, Daniel; Thielemans, Wim; Riffat, Saffa (Elsevier, 2017)
This article investigates impact of substituting fumed silica with a cellulosic-crystal innovation in a commercial Vacuum Insulated Panel (VIP) core. High building performance demands have attracted VIP technology investment to increase production capacity and reduce cost. In building retrofit VIPs resolve practical problems on space saving that conventional insulations are unsuitable for. Three challenges exists in fumed silica: cost, low sustainability properties, and manufacture technical maturity. Cellulosic nano-crystal (CNC) technology is in its infancy and was identified as a possible alternative due to a similar physical nano-structure, and biodegradability. The study aim was to determine a performance starting point and establish how this compares with the current benchmarks. Laboratory cellulosic-crystal samples were produced and supplied for incorporation into commercial VIP manufacture. A selection of cellulosic-panels with core densities ranging 127–170 kg/m3 were produced. Thermal conductivities were tested at a pressure of 1 Pa (0.01 mBar), with the results compared against a selection of fumed silica-VIPs with core densities ranging 144–180 kg/m3. Conductivity tests were then done on a cellulosic-VIP with 140 kg/m3 density, under variable pressures ranging 1–100,000 Pa (0.01–1000 mBar). This investigated panel lifespan performance, with comparisons made to a fumed silica-VIP of similar core density. Manufactured cellulosic-samples were found unsuitable as a commercial substitute, with performance below current standards. Areas for cellulosic nano-material technology development were identified that show large scope for improvement. Pursuit could create a new generation of insulation materials that resolve problems associated with current commercial versions. This is most applicable in building retrofit where large ranges of domestic and commercial cases are marginalised from their construction markets due to impracticalities and high upgrade costs. This being a problem in multiple economies globally.